Second Survey of County Health Departments of Kansas and COVID 19: Time for Change in Model for Pandemic Response - Raghuveer, Talkad S; Zackula, Rosey; Wittler, Robert (Kansas Journal of Medicine, 2020)
Introduction. SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) causing COVID-19 (Coronavirus Disease 2019) continues to be widespread in Kansas. County health departments are trying to contain this pandemic. Methods. This second survey of Kansas county health department directors occurred from August 7 to September 7, 2020. Since the first survey in April, there have been significant increases in the number of positive cases of COVID-19 and related deaths. Thus, the aim of the study was to re-evaluate county-level containment efforts and assess shortfalls that were previously identified in the April 2020 survey. Results. In total, 41 out of 105 directors responded to the survey. Generally, respondents said there were increased supplies for testing, increased testing centers, shorter time to get test results, and in some cases, increased funding. However, the number of people involved in contact tracing had not substantially increased, which was one of the recommended changes for improving containment. Moreover, of those persons who were tested, only a few (18%) counties inquired if they wear masks in public. From comments reported, there was a sense of employees being overwhelmed, especially among the smaller county health departments. Conclusions. As the cases of and deaths from COVID-19 are increasing in the state, especially in high density areas, the respondents to our survey indicate there is continued need for additional funding with easy access, increased staffing, especially for contact tracing, and significant help for effective messaging to improve adherence to public health directives.